2008
DOI: 10.2105/ajph.2006.097097
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Among US Children With Different Types of Disabilities

Abstract: Children with certain types of disabilities are at a significantly higher risk of injuries than are children without disabilities, but the characteristics of injuries are similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 25 publications
4
37
0
4
Order By: Relevance
“…5,7,11,12,14,17,23,30 In a study using NHIS data, Brophy et al 12 reported injury odds ratios of 1.68 and 2.98 for moderate and severe disability, respectively, which is comparable to our study's adjusted odds ratio of 2.35 for workers with disabilities for nonoccupational injuries. Furthermore, our data show a higher rate of occupational injuries among workers with disabilities than workers without disabilities.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…5,7,11,12,14,17,23,30 In a study using NHIS data, Brophy et al 12 reported injury odds ratios of 1.68 and 2.98 for moderate and severe disability, respectively, which is comparable to our study's adjusted odds ratio of 2.35 for workers with disabilities for nonoccupational injuries. Furthermore, our data show a higher rate of occupational injuries among workers with disabilities than workers without disabilities.…”
Section: Discussionsupporting
confidence: 82%
“…One current conceptualization of disability, the World Health Organization's International Classification of Functioning, Disability and Health (ICF), emphasizes environmental factors and has been used in recent studies to evaluate injury risks of persons with disabilities. 10,12,23 The ICF defines disability as physical impairments, activity limitations, and participation restrictions that affect one's interaction with the physical and social environment.…”
mentioning
confidence: 99%
“…Nevertheless, this finding was consistent with our hypothesis. Research has shown (Sinclair & Xiang, 2008;Szilagyi et al, 2003) that children with disabilities are at increased risk for obesity, injuries, poorer overall health, and less preventive care and immunizations (Perrin, 2002) than their nondisabled peers (Szilagyi et al, 2003). To ameliorate these adverse outcomes, periodic health and developmental screening, referral for specialty care, and anticipatory guidance around health promotion have been recommended (American Academy of Pediatrics Medical Home Initiatives for Children With Special Needs Project Advisory Committee, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study conducted by Xiang and colleagues reported an increased risk of nonfatal injuries among children, aged 5-17 years, with chronic asthma, vision/hearing disability and ADHD (Xiang, Stallones, Chen, Hostetler & Kelleher, 2005). A second study by Sinclair and Xiang found an increased risk of injury for any single disability (all single disabilities combined) and for emotional or behavioral problems (Sinclair & Xiang, 2008). An earlier study identified a statistically significant increase in injury rate among children with developmental disabilities but only among children aged 0-5 years, (Dunne, Asher & Rivara, 1995).…”
Section: Introductionmentioning
confidence: 99%